Empresarios españoles de ida y vuelta en el México porfiriano y en la España de la Restauración - Carlos Marichal (Les Cahiers ALHIM)
The historical analysis of the careers of emigrants who left their home countries to find better opportunities abroad in the nineteenth and twentieth centuries demonstrates that they were marked by a variety of experiences, including economic success or failure. In the case of most studies on those individuals who attained wealth and a high social position attention is generally centered on  their trajectories in the country to which they emigrated.  In contrast, less attention is devoted to their careers on returning to their home country, if they did so return.  This study proposes to highlight the economic role of Spaniards who migrated to Spanish America both in the country to which they emigrated as well as in their native country. In this  essay,  l study the career of Antonio Basagoiti y Arteta, a Spanish entrepreneur, who arrived to Mexico  1870s and rapidly passed from small to large merchant banker, soon becoming a prominent figure  in several of the leading credit institutions of  Porfirian Mexico. He was a director of the most important Mexican bank of the day, Banco Nacional de México, but later also became the founder in 1901 of the Banco Hispano Americano in Madrid, an institution that would soon become one of the most powerful commercial banks in Spain. In the process, Basagoiti built up a complex and efficient network of kinship and commercial relations that contributed to his participation  in the upper echelons of business in the late nineteenth century Mexico but also in early twentieth century Spain. We hope that our study will allow historians, sociologists and other scholars of the life and career of immigrants- who became entrepreneurs- to assess the possibility of extending  case studies to include their career trajectories after return to their countries of origin.